Eksplorasi Wisata Religi Makam Maulana Malik Ibrahim Gresik Sebagai Destinasi Wisata Halal - Hakim, Abdul; Nurlailah, Nurlailah; Rahmawati, Lilik; Mustofa, Imam Ali (Indonesia Journal of Halal, 2024)
The development of world tourism today is Muslim-friendly tourism. The realization of religious tourism as Muslim-friendly religious tourism is a necessity. This research focuses on exploring the tourism services and facilities of Maulana Malik Ibrahim Sunan Giri Gresik referring to the nine indicators of Indonesian halal tourism and assessing the readiness of Gresik religious tourism as a halal tourism destination. The research method used is qualitative. Data collection techniques through field studies and documentation. Field studies were conducted through interviews and observations. Field studies were conducted through interviews and observations. Interviews were conducted with the Head of the Gresik Regency Tourism and Culture Office, the Head of the Sunan Giri Tomb Foundation. Observations made include observing the availability of facilities and services around the Sunan Giri religious area referring to the nine halal tourism indicators of the Indonesian Ministry of Tourism and Creative Economy. The results showed that Sunan Giri Gresik religious tourism is ready to be projected as a halal tourist destination because it has fulfilled nine indicators of Indonesian halal tourism. Sunan Giri religious tourism also has advantages in terms of more complete facilities and infrastructure, such as: souvenirs, human resources, service models, management standards, availability of lodging and transportation.